Morphological plasticity of endophytic Chitinophaga pinensis - Janine Liedtke; Frans Rodenburg; Chao Du; Le Zhang; Jos M. Raaijmakers; Gilles P. van Wezel; Ariane Briegel (Antonie van Leeuwenhoek, 2026)
Environmental changes, whether due to climate change or human influences, compromise the resilience of plants to biotic and abiotic stresses, such as pathogens, drought and heat. Plant microbiota are known to promote plant resilience. To be able to harness the power of the plant microbiome we need to identify microbiota with health-promoting properties. Recent studies have demonstrated that the bacterium Chitinophaga pinensis enhances plant health and increases resistance to fungal infections. Here, we show that C. pinensis exhibits an unusually high morphological plasticity, switching between a filamentous and a spherical cell state, each of which is characterized by a distinct transcriptional profile. Despite these transcriptional differences, spherical cells remained metabolically active and replicating, while lacking structural characteristics typically associated with dormant states. Furthermore, the spherical cell morphology of C. pinensis facilitates hitchhiking behaviour and motility via surfactin cheating, potentially influencing its dispersal and interactions within the plant microbiome. To investigate the structural dynamics and transcriptional adaptation of this plant endophyte, we applied a combination of microscopy and culture-based techniques. Taken together, our study provides new insights into the morphological flexibility and transcriptional regulation of the plant-beneficial C. pinensis .